(untitled) (Gaceta de Ciencias Veterinarias, 2015)
The sperm is a highly specialized cell and their metabolic activity varies according to different stages of the life of the sperm which is determined by signals from the environment that surrounds them in order to achieve fertilization. Sperm requires an energy metabolism to generate enough free energy for mobility flagellar, which occurs most efficiently in aerobic conditions, mainly due to oxidative phosphorylation, mitochondria which are found in the part-level intermediate of the scourge, however, this is not enough to achieve the hyperactivity of the movement flagellar during training, so the main piece has all the enzymatic machinery to generate ATP from glycolysis which is fundamental to the process of fertilization.